Life Within a Contaminated Niche: Comparative Genomic Analyses of an Integrative Conjugative Element ICEnahCSV86 and Two Genomic Islands From Pseudomonas bharatica CSV86T Suggest Probable Role in Colonization and Adaptation - Mohapatra, Balaram; Malhotra, Harshit; Phale, Prashant S. (Frontiers in Microbiology, 2022)
Comparative genomic and functional analyses revealed the presence of three genomic islands (GIs, >50 Kb size): ICEnahCSV86, Pseudomonas bharatica genomic island-1 (PBGI-1), and PBGI-2 in the preferentially aromatic-degrading soil bacterium, Pseudomonas bharatica CSV86T. Site-specific genomic integration at or near specific transfer RNAs (tRNAs), near-syntenic structural modules, and phylogenetic relatedness indicated their evolutionary lineage to the type-4 secretion system (T4SS) ICEclc family, thus predicting these elements to be integrative conjugative elements (ICEs). These GIs were found to be present as a single copy in the genome and the encoded phenotypic traits were found to be stable, even in the absence of selection pressure. ICEnahCSV86 harbors naphthalene catabolic (nah-sal) cluster, while PBGI-1 harbors Co-Zn-Cd (czc) efflux genes as cargo modules, whereas PBGI-2 was attributed to as a mixed-function element. The ICEnahCSV86 has been reported to be conjugatively transferred (frequency of 7 × 10–8/donor cell) to Stenotrophomonas maltophilia CSV89. Genome-wide comparative analyses of aromatic-degrading bacteria revealed nah-sal clusters from several Pseudomonas spp. as part of probable ICEs, syntenic to conjugatively transferable ICEnahCSV86 of strain CSV86T, suggesting it to be a prototypical element for naphthalene degradation. It was observed that the plasmids harboring nah-sal clusters were phylogenetically incongruent with predicted ICEs, suggesting genetic divergence of naphthalene metabolic clusters in the Pseudomonas population. Gene synteny, divergence estimates, and codon-based Z-test indicated that ICEnahCSV86 is probably derived from PBGI-2, while multiple recombination events masked the ancestral lineage of PBGI-1. Diversifying selection pressure (dN-dS = 2.27–4.31) imposed by aromatics and heavy metals implied the modular exchange-fusion of various cargo clusters through events like recombination, rearrangement, domain reshuffling, and active site optimization, thus allowing the strain to evolve, adapt, and maximize the metabolic efficiency in a contaminated niche. The promoters (Pnah and Psal) of naphthalene cargo modules (nah, sal) on ICEnahCSV86 were proved to be efficient for heterologous protein expression in Escherichia coli. GI-based genomic plasticity expands the metabolic spectrum and versatility of CSV86T, rendering efficient adaptation to the contaminated niche. Such isolate(s) are of utmost importance for their application in bioremediation and are the probable ideal host(s) for metabolic engineering.